Presumed missense and synonymous mutations in ATP7B gene cause exon skipping in Wilson disease. (2nd May 2018) - Wang, Chunli; Zhou, Wei; Huang, Yan; Yin, Hanjun; Jin, Yu; Jia, Zhanjun; Zhang, Aihua; Liu, Zhifeng; Zheng, Bixia
Abstract: Background & Aims: Wilson disease is an inborn error of metabolism caused by abnormalities of the copper‐transporting protein‐encoding gene ATP7B . Recently, the phenomenon of exon skipping, in which exonic mutations result in abnormal splicing, has been associated with various diseases. The present study investigated the splicing defects of the ATP7B exonic variants identified in a cohort of 44 patients with Wilson disease. Method: All patients were analysed for ATP7B gene by direct sequencing or multiplex ligation‐dependent probe amplification analysis. To identify the potential pathogenicity of the candidate mutations that may induce exon skipping, both in vivo RT‐PCR analysis using RNA from peripheral leukocytes and in vitro functional splicing by minigene construction were conducted. Results: The patterns of inheritance of the mutations in ATP7B identified in 44 patients exhibited homozygotes (7 patients), compound heterozygotes (32 patients) and heterozygotes (5 patients). In all patients, we detected 25 different ATP7B mutations, including 17 missenses, 1 frameshift, 3 nonsenses, 2 exonic deletions and 2 splicing alteration. In these mutations, 4 mutations have not been previously described in the literature or entered in human genome mutation database. Furthermore, we identified synonymous mutation c.4014T>A and missense mutation R919G caused exon skipping in the ATP7B mRNA transcript. Conclusion: Our results suggest that aberrant exon skipping associated to putative splicing enhancer disruption and silencer creation is one previously unrecognized mechanism in Wilson disease. What is more, the multiplex ligation‐dependent probe amplification assay for the detection of exon deletions may be valuable in individuals with clinical Wilson disease diagnosis where one or no mutation has been identified by sequencing. Abstract : See Editorial on Page 1375